Effects of Papaya Seed Oil (Carica papaya Linn.) on Food Consumption, Weight Gain and Hormones of Animals Treated With a High Calorie Diet. (7th June 2021) - Santana, Lidiani; Aquino, Diana; Santo, Bruna Espirito; Guércio, Adriana; Tatara, Mariana; Croda, Júlio; Guimarães, Rita de Cássia; Freitas, Karine; Hiane, Priscila
Abstract: Objectives: To evaluate the effects of papaya seed oil (Carica papaya Linn.) on food consumption, weight gain and hormonal of animals treated with a high calorie diet. Methods: The project was approved by protocol n o 980/2018 (CEUA). Swiss, male, adult mice were used and divided into the experimental groups: control group (CT - Nuvital® diet - saline treatment), AIN-93M group (AIN-93M diet - saline treatment), HPL group (hypercaloric diet - saline treatment), HPL OS group (hypercaloric diet - soybean oil treatment), HPL AZ group (hypercaloric diet - olive oil treatment) and HPL OM group (hypercaloric diet - papaya seed oil treatment). The animals received treatment daily by gavage, 1 mL/kg, for 8 weeks. Body weight and food consumption were evaluated (Camry® analytical digital scale). At the end of the experiment, the animals were submitted to euthanasia and the blood was collected for quantification of leptin, insulin and resistin (commercial kit MADKMAG-71K®-Merck). The results were expressed as mean ± standard deviation, using Prisma 5.0 software (GraphPad Software, USA) ( P  ≤ 0.05).It was observed that the papaya seed oil reduced food consumption and body weight, as well as increased the concentration of leptin, maintaining insulin and resistin, thus being effective in combating the metabolic changes caused by the high fat diet. Results: In the first month of the study, food consumption was lower in the HPL AZ and HPL OM groups than in the CT ( P  < 0.005), and in the second month all groups that received HPL diet consumed less if compared to the CT, being that HPL OM have significantly lower consumption than groups AIN-93M,  CT and HPL ( P  < 0.05). At the beginning of the experiment, all animals were weighed and evenly distributed in the groups ( P  = 0.938). In the first and second weeks, HLP OM had a lower weight than HLP OS and HPL ( P  < 0.05). In the weeks that followed, the weight gain of the HLP OM group was lower compared to the groups that received a high-fat diet, but without significant difference. In the evaluation of the hormone leptin, a higher value was found in the HPL OM group ( P  < 0.001), with values of resistin and insulin similar to the control groups. Conclusions: It was observed that the papaya seed oil reduced food consumption and body weight, as well as increased the concentration of leptin, maintaining insulin and resistin. Funding Sources: CNPQ.